Comprehensive analysis of disulfidptosis-related genes and the immune microenvironment in heart failure - Linna Zhao; Juanjuan Zhang; Juanjuan Zhang; Qiuhang Song; Cheng Dai; Yiping Qin; Aiying Li; Aiying Li (Frontiers in Cell and Developmental Biology)
BackgroundHeart failure (HF) is a prevalent cardiovascular disease that currently lacks effective treatment options due to its intricate pathogenesis. A recent study has linked disulfidoptosis, a novel form of cell demise, with the development of a range of diseases. Nonetheless, the effect of disulfidoptosis on the immune microenvironment of HF is not well comprehended. In this paper, bioinformatics analysis was performed to investigate how disulfidptosis-related genes (DRGs) affect the immune microenvironment of HF.MethodsThe expression of four DRGs was initially examined using bulk RNA-Seq and single-cell RNA sequencing data. A predictive model was subsequently developed. Consensus clustering was used to distinguish between the two clusters of DRGs. The effect of these DRGs on the characteristics of the immune microenvironment was further explored, such as infiltrating immune cells, immune response gene sets, and HLAs genes.ResultsAll four DRGs were dysregulated in HF samples. The predictive model based on these four DRGs effectively differentiated between HF patients and healthy individuals, which was validated in the experiment. These four DRGs were strongly associated with the abundance of infiltrating monocytes. Moreover, our analysis identified two distinct clusters of DRGs and these clusters exhibited differences in terms of immune cell abundance, immune response, and HLA gene expression. The biological functions associated with these differences were also revealed.ConclusionOur discovery underscores the pivotal role of DRGs in shaping the diversity and intricacy of the immune microenvironment in HF.